2001
DOI: 10.2169/internalmedicine.40.127
|View full text |Cite
|
Sign up to set email alerts
|

Sarcoid Reaction in Primary Tumor of Bronchogenic Large Cell Carcinoma Accompanied with Massive Necrosis.

Abstract: A 49-year-old womanconsulted our hospital for evaluation of a tumor with cavitation in the S6 segment of the right lung. She was given a diagnosis of pulmonary tuberculoma because percutaneous needle aspiration cytology revealed epithelioid cells with a background of necrosis. However, a diagnosis of large cell carcinoma with central necrosis (p-T2N0M0) was established by thoracoscopic lung biopsy six months later. Pathological findings of surgical resection specimens showed that epithelioid cell granulomas ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
(7 reference statements)
0
3
0
Order By: Relevance
“…Since no pulmonary, skin or ocular lesions indicative of systemic sarcoidosis were seen in this patient, a diagnosis of composite exocrine-endocrine gastric carcinoma associated with sarcoid reaction was established. It has been suggested that sarcoid reactions may be caused by soluble antigenic factors derived from tumor cells [30]. Sarcoid reaction might be a marker of an immunologically mediated anti-tumor response of macrophages activated by T lymphocytes that may influence longer survival [30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since no pulmonary, skin or ocular lesions indicative of systemic sarcoidosis were seen in this patient, a diagnosis of composite exocrine-endocrine gastric carcinoma associated with sarcoid reaction was established. It has been suggested that sarcoid reactions may be caused by soluble antigenic factors derived from tumor cells [30]. Sarcoid reaction might be a marker of an immunologically mediated anti-tumor response of macrophages activated by T lymphocytes that may influence longer survival [30].…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that sarcoid reactions may be caused by soluble antigenic factors derived from tumor cells [30]. Sarcoid reaction might be a marker of an immunologically mediated anti-tumor response of macrophages activated by T lymphocytes that may influence longer survival [30]. The possibility of associated Crohn's disease was excluded due to the absence of other characteristic features, except granulomas: "cobblestone" mucosa, wall stiffness, luminal stenosis and histologically-submucosal edema and fibrosis with lymphangiectasia, transmural chronic inflammation with lymphoid aggregates, fissuring ulcers, and neuronal hyperplasia [31].…”
Section: Discussionmentioning
confidence: 99%
“…On occasion, systemic tumors induce microgranuloma formation in lymph nodes within their drainage distribution, but their occurrence within the substance of these tumors is very uncommon [36][37][38]. The basis for the reaction is unclear.…”
Section: Discussionmentioning
confidence: 99%